Unveiling the diversity and ecological roles of macrofungi in Ayer Hitam Forest Reserve, Selangor, Malaysia - Mohd Nordin, Noor Aisyah; Mohd Zainudin, Nur Ain Izzati; Syazwan, Wan Mohd; Abd Aziz, Nor Azwady (Malaysian Society of Applied Biology, 2024)
The biodiversity of macrofungi in remaining lowland dipterocarp forest in highly urbanization pressures is infrequently studied, even though their significant impact on the ecosystem of forested and non-forested habitats. Therefore, this research endeavours to unravel the diversity of macrofungi from different substrates in the Ayer Hitam Forest Reserve located in Selangor, Malaysia. Through a combination of field surveys, the study seeks to contribute valuable insights into the complex relationships between macrofungi and the surrounding habitats where macrofungal community structure was mainly influenced by substrate richness and microclimates. Sporocarps of macrofungi were collected from selected sites using opportunistic sampling methods. A total of 333 sporocarps were obtained and identified based on morphological and molecular analysis. Basidiomycota prevailed in the Ayer Hitam Forest Reserve where 27 species belonging to 14 families were successfully identified. Saprophytic fungi (22 species, 81.5%) dominated the areas, and a small number of mycorrhizal (1 species, 3.7%) and parasitic (4 species, 14.8%) fungi were found. Based on species diversity, order Polyporales is the highest occurrence species in the sampling areas with a Shannon-Weiner Index value of 2.103 and Simpson Index value of 0.954, Evenness Index value of 0.601, making it the most abundant order containing Microporus species, The findings are expected to enhance our knowledge of the biodiversity of macrofungi from different substrates in Ayer Hitam Forest Reserve, which can lead to conservation efforts and promote the ecological significance of macrofungi in tropical forest ecosystems.